Influence of Scaffold Structure and Biomimetic Properties on Adipose Stem Cell Homing in Personalized Reconstructive Medicine - Doina Ramona Manu; Diana V. Portan; Monica Vuţă; Minodora Dobreanu (Biomimetics)
Human adipose stem cells (ASCs) are multipotent cells expressing mesenchymal stem cell (MSC) markers that are capable of multilineage differentiation and secretion of bioactive factors. Their “homing” to injured tissues is mediated by chemokines, cytokines, adhesion molecules, and signaling pathways. Enhancing ASC homing is critical for improving regenerative therapies. Strategies include boosting chemotactic signaling, modulating immune responses to create a supportive environment, preconditioning ASCs with hypoxia or mechanical stimuli, co-culturing with supportive cells, applying surface modifications or genetic engineering, and using biomaterials to promote ASC recruitment, retention, and integration at injury sites. Scaffolds provide structural support and a biomimetic environment for ASC-based tissue regeneration. Natural scaffolds promote adhesion and differentiation but have mechanical limitations, while synthetic scaffolds offer tunable properties and controlled degradation. Functionalization with bioactive molecules improves the regenerative outcomes of different tissue types. Ceramic-based scaffolds, due to their strength and bioactivity, are ideal for bone healing. Composite scaffolds, combining polymers, ceramics, or metals, further optimize mechanical and biological properties, supporting personalized regenerative therapies. This review integrates concepts from cell biology, biomaterials science, and regenerative medicine to offer a comprehensive understanding of ASC homing and its impact on tissue engineering and clinical applications.